Adsorption properties of CH4 and CO2 in quartz nanopores studied by molecular simulation. Issue 39 (4th April 2016) - Sun, Haoyang; Sun, Wenchao; Zhao, Hui; Sun, Yange; Zhang, Dianrui; Qi, Xiaoqing; Li, Ying
Abstract : Competitive adsorption isotherms and adsorption density distributions of binary mixtures containing CH4 and CO2 in nanopores with 100% and 60% surface hydroxylation at 323 K. Abstract : In this work, grand canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulation methods were used to study the adsorption properties of CH4 and CO2 as single components and binary mixtures in modeled quartz nanopores ( d ∼ 2 nm), of which the surface was hydroxylated to different degrees. The variation of the adsorption and molecular diffusion characteristics of CH4 and CO2 as a function of temperature and pressure were determined, and the competitive adsorption of CH4 and CO2 was investigated. As single components, both the adsorption of CH4 and CO2 in the nanopore is described well by the Langmuir model, and the diffusion capacities of the gas molecules in a non-supercritical state are much larger than that in a supercritical state. It was found that there is a tight adsorption layer of CH4 with a thickness of 3–5 Å in the nanopore, while CO2 molecules adsorb tightly as a whole phase, especially in the supercritical fluid state. In the binary mixed system, CO2 preferentially adsorbs to the nanopore surface compared to CH4 due to the strong interactions between the CO2 molecule and the hydrophilic groups on the pore surface. An obvious competitive adsorption of CO2 and CH4 occurs at certain temperature ranges (313–353 K) with increasing pressure. And the degree of surface hydroxylation has significant contributions to the adsorption selectivity of CO2 over CH4 . This work provides microscopic information about adsorption properties of CH4 and CO2 in nanopores at the molecular level for the purpose of guidance towards the application of shale gas extraction by flowing CO2 .